MA'HAD Al-JAMI’AH IN INDONESIA: PORTRAIT OF THE ARABIC LANGUAGE LEARNING MODEL - Sodik, Achmad Ja'far; Hermawan, Hermawan; Musta'in, Musta'in (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2023)
The study aims to identify the tangible forms of Arabic language learning programs and to describe the models of Arabic language learning at the ma’had al-jamiah of Fatmawati Sukarno Bengkulu State Islamic University and Ali Bin Abi Thalib Surabaya Islamic College. This research adopts a descriptive qualitative type. The sources of information include observations during the Arabic language learning process and interviews with instructors or teachers. The Data analysis in this research is conducted using the interactive analysis theory by Miles and Huberman. The analysis technique involves data collection, presentation, reduction, and conclusion. The results of this research indicate that: Firstly, the forms of Arabic language learning programs at the ma’had al-jamiah of Fatmawati Sukarno Bengkulu State Islamic University include: ta’lim al-lughoh al-arabiyah, muhadtsah yaumiyah fi al-lughoh al arabiyah, provision of vocabularies, and khitabah. The forms of Arabic language learning programs at the ma’had al-jamiah of Ali bin Abi Thalib Surabaya Islamic College include: insya bi’ah lughowiyah, fashl ilaaji, fashl idhofi, muhadharah arabiyah, and muhadtsah usbuiyah. Secondly, the models of Arabic language learning at the ma’had al-jamiah of Fatmawati Sukarno Bengkulu State Islamic University and Ali bin Abi Thalib Surabaya Islamic College include direct learning and learning with presentations.